Cryolithostratigraphy of the Middle Pleistocene to Holocene Deposits in the Dmitry Laptev Strait, Northern Yakutia - Tumskoy, Vladimir; Kuznetsova, Tatiana (Frontiers in Earth Science, 2022)
The northernmost part of continental Yakutia in the Dmitry Laptev Strait region developed under non-glacial conditions during the Quaternary period. During cooling periods, ice-rich deposits with syngenetic ice wedges, called the Ice Complex, formed here. During periods of warming, they partially thawed under thermokarst lakes and a peculiar complex of lacustrine-boggy deposits (the Alas Complex) was formed. The article presents a description of ice-rich deposit sequences in several Ice Complex horizons and their transformation in lake taliks from the Middle Pleistocene to the Holocene (MIS 7—MIS 1). The Oyogos Yar section structure is considered as an example using additional geological data from the southern coast of Bol’shoy Lyakhovsky Island. Specific examples show the results of changes in the structure of sections via cryogenic processes—ice wedge formation and thawing. We confirm that cryogenic processes are important factors, along with accumulation and erosion processes, which change the geological and cryolithological structure of the sections. It is shown that to clearly understand the stratigraphic subdivision of Quarternary deposits in areas of Ice Complex development, geological and analytical studies of the sections are insufficient; an elucidation of the sequence of sediment freezing and thawing and the resulting cryolithogical phenomena is necessary.